The Role of Public Policy in the Development of Technological Capabilities of Companies in the Wind Energy Sector and the Impact on Social and Environmental Performance - Melo, José Maria Gonçalves Nunes de; Câmara, Samuel Façanha; Farias, FabÃola Gomes; Lima, Fábio Nóbrega de; Freitas, Ana Augusta Ferreira de (International Journal of Energy Economics and Policy, 2017)
The object of this study was to analyze the role of public policies in the development of technological capacities in firms of the wind energy sector and the impacts of this development in social and environmental performances of these firms. The investigation was organized through semi-structured interviews with ten professionals of political policies in different Brazilian states and seven professionals of wind energy corporations in Brazil. The main implications in the field of public policies reveal they were fundamental for the sectors development, but were inefficient regarding the transfer of technology to Brazil, training and qualification of the workforce, development of the infrastructure to the wind energy sector, and the development of technological capacities of the firms. Keywords: Wind energy policy. Technological capacity. Social and environmental performance JEL Classifications: Q42, Q48, Q55, Q56